Saberes e práticas de enfermeiras acerca do acolhimento com classificação de risco em centro obstétrico - Ilha, Caroline Bolzan (2017)
It`s a qualitative descriptive field research performed with 11 labor ward nurses in a teaching hospital. The question that guided this study was: What is the knowledge and the practices of the nurses about user embracement with risk assessment in a labor ward. The objective was to understand the knowledge and the practices of the nurses about user embracement with risk assessment. The data production happened between May and June, 2016 through a focus group. The data were submitted to the operative proposal. The project was approved by the Research Ethics Committee under the CAAE number 53781516.0.0000.5346. Three categories emerged from the results: conceptualizing user embracement with risk assessment: a group construction; easiness and difficulties experienced by nurses on user embracement with risk assessment; the user embracement with risk assessment as a path. The findings indicate that the nurse`s knowledge is related to the main recommended instructions by Brazil`s women`s health care policies and programs. Furthermore, facilitating and complicating aspects have arisen, which pointed to some challenges to be overcome during the practice of care, like overcrowding, disjointed work, conflicts and disparities of power, disorganization of the gateway and the risk assessment, disrespect to the nurses' autonomy and the lack of articulation with the rest of the health network. It's necessary to rethink and also to create new ways of acting in healthcare so as to reflect on a humanizing, effective and welcoming treatment by understanding the importance of the alliance between the services available in the local network, bond strengthening and the proximity between the involved individuals.